1996
DOI: 10.1021/jp961434c
|View full text |Cite
|
Sign up to set email alerts
|

Modeling with Special Descriptors Derived from a Medium-Sized Set of Connectivity Indices

Abstract: The descriptive and utility power of linear combinations of special construction of connectivity indices (LCXCI) derived by a trial-and-error procedure from a medium-sized set of eight connectivity indices or from a subset of it has been tested on several properties of different classes of bioorganic and inorganic compounds. Two techniques have been tested to choose the appropriate combination of indices:  the forward selection and the complete combinatorial technique. While the latter searches the entire comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 26 publications
(45 reference statements)
0
112
0
Order By: Relevance
“…[10][11] has come out to be 67.18. From these values we can infer that the six parametric model is the best for modeling the present set of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11] has come out to be 67.18. From these values we can infer that the six parametric model is the best for modeling the present set of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The R 2 pred value based on the combination of both the types if descriptors was found to be 0.9614.Once again we observed that topological indices exhibit better predictive power compared to structural descriptors. The predictive power is further confirmed by calculating Pogliani's quality factor (Q) [41][42][43] . The Q values are reported under each of the proposed models indicating that the predictive power goes on increasing as we go from mono-to tetra-parametric models and is highest for the latter.…”
Section: Predictive Power Of the Modelmentioning
confidence: 85%
“…Multiple linear regressions are used to develop these models. The predictive potential of these models are discussed on the basis of quality factor (Q) 28,29 .…”
Section: Methodsmentioning
confidence: 99%